Nyord og allmenne ordbøker - Eek, Øystein (Nordiske Studier i Leksikografi, 2006)
Neologisms and general dictionaries. The article presents a survey that was carried out among editors at Kunnskapsforlaget concerning neologisms in the Norwegian language. The editors were asked to mark which of the neologisms they would insert in general monolingual dictionaries. At the NFL Conference in Sønderborg 2005, the same test was done with the audience. The results are compared with the editors’ survey and some comments are made on how academic lexicographers and commercial lexicographers and encyclopaedia editors evaluate which neologisms are most useful.